KKN-PPM Pengembangan Rumah Pangan dan Klinik Tumbuhan Obat untuk Pemenuhan Pangan dan Gizi serta Peningkatan Derajat Kesehatan Masyarakat Berbasis Education for Sustainable Development - Rahmawati, Sitti; Hasriyanty, Hasriyanty; Panggeso, Johanis (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
This real working lecture program - community empowerment learning was aimed at assisting the target community in developing Lestari House of Food (LHF) and Clinic of medicinal plants to meet the needs for food and nutrition and to increase the community?s health on the basis of Education for Sustainable Development (ESD). Through this program, the target community would increase their knowledge and skills in utilizing local resources optimally, especially in managing lands intensively. To achieve the program objectives, there was empowering program done to the target groups, including (a) disseminating the real working lecture program - community empowerment learning to the regional Government, especially to related technical units, local Government, and target groups, (b) extension regarding to the importance of utilizing lands intensively in developing Lestari House of Food and the clinic of medicinal plants, (c) participatory training to improve skills of the target groups in identifying potencies, problems, and opportunities of business development, as well as planning, actuating, monitoring, and evaluating programs / activities,  (d) technical training for Lestari House of Food and medicinal plants clinic, and (e) assistance in managing the land intensively by involving resources namely families and target community group in participatory method. The goal achieved by this program was the increase in knowledge and skills of the community in utilizing the potential resource in the form of lands to improve their income and prosperity on the basis of technological innovation and local wisdom, which is oriented to Education for Sustainable Development.